HUMANISASI RUANG DIGITAL: PENGARUH PSYCHOLOGICAL SAFETY DALAM DISKUSI ASYNCHRONOUS TERHADAP KETERLIBATAN MAHASISWA - Galuh Latifah; Umu Salamah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Digital transformation in education often neglects the humanization aspect, thus triggering a passive learning atmosphere for students. This study aims to examine the effect of psychological safety on student engagement in an asynchronous discussion forum based on humanistic learning theory. This study used a quantitative approach with an explanatory survey method. All data were collected through a 1-5 Likert scale questionnaire distributed to students. The data analysis techniques applied were descriptive analysis and simple linear regression to prove the hypothesis testing. The results showed that the average value of psychological safety and student engagement views were in the high category. The results of the research with regression analysis produced a determinant coefficient of 0.468, proving that psychological safety contributed 46.8% to the formation of significant student engagement. This is a new finding that the development of a threat-free, inclusive, and error-tolerant academic climate is the main key to driving student cognitive investment in the digital space. The implications of this research direct educators to integrate humanistic values in the management of online forums to optimize students' active learning participation.